Venous sinus stenting as a treatment approach in patients with idiopathic intracranial hypertension and encephaloceles. Issue 1 (February 2021) - Drocton, Gerald T; Copelan, Alexander; Eisenmenger, Laura; Villanueva-Meyer, Javier E; Dillon, William P; Shah, Vinil N; Meisel, Karl; Amans, Matthew
Background: Stenosis of a dural venous sinus is the most common cause of idiopathic intracranial hypertension (IIH) and can be classified as either intrinsic or extrinsic. Intrinsic stenoses are characterized by a focal filling defect within the sinus secondary to an enlarged arachnoid granulation or fibrous septa while extrinsic stenoses tend to be long and smooth-tapered and are most commonly secondary to external compression from the adjacent brain parenchyma. Brain herniations, or encephaloceles, into arachnoid granulations in dural venous sinuses have rarely been reported in the literature in patients with IIH. We propose that dural venous sinus stenting (VSS) may be a safe and effective treatment approach in patients with an encephalocele and IIH. Methods: We retrospectively analyze three cases of patients with encephalocele who underwent VSS for treatment of medically refractory IIH at our institution. Results: One patient underwent stenting ipsilateral and two patients underwent stenting contralateral to the side of their encephaloceles. No technical related issues or complications occurred during either of the three stenting procedures. Two out of the three patients had complete resolution in their IIH-related symptoms and normalization of cerebrospinal (CSF) pressures shortly after stenting. We await clinical follow-up in the third patient. Conclusions: Our results suggest that VSS is a technically feasible and effective approach in treating patients with medically refractory IIH and encephaloceles.